Contributions of Different Sea‐Level Processes to High‐Tide Flooding Along the U.S. Coastline. Issue 7 (14th July 2022) - Li, S.; Wahl, T.; Barroso, A.; Coats, S.; Dangendorf, S.; Piecuch, C.; Sun, Q.; Thompson, P.; Liu, L.
Abstract: Coastal communities across the United States (U.S.) are experiencing an increase in the frequency of high‐tide flooding (HTF). This increase is mainly due to sea‐level rise (SLR), but other factors such as intra‐ to inter‐annual mean sea level variability, tidal anomalies, and non‐tidal residuals also contribute to HTF events. Here we introduce a novel decomposition approach to develop and then analyze a new database of different sea‐level components. Those components represent processes that act on various timescales to contribute to HTF along the U.S. coastline. We find that the relative importance of components to HTF events strongly varies in space and time. Tidal anomalies contribute the most along the west and northeast coasts, where HTF events mostly occur in winter. Non‐tidal residuals are most important along the Gulf of Mexico and mid‐Atlantic coasts, where HTF events mostly occur in fall. We also quantify the minimum number of components that were required to cause HTF events in the past and how this number changed over time. The results highlight that at present, due to SLR, fewer components are needed to combine to push water levels above HTF thresholds, but tidal anomalies alone are still not sufficient to reach HTF thresholds in most locations. Finally, we explore how co‐variability between different components leads to compounding effects. In some places, positive correlation between sea‐level components leads to significantly more HTF events than would be expected if sea‐level components were uncorrelated, whereas in other places negative correlation leads to fewer HTF events. Plain Language Summary: High‐tide flooding, also known as nuisance flooding or minor flooding, is one of the most obvious outcomes of climate change and associated sea‐level rise (SLR). The increased frequency of high‐tide flooding (HTF) and the fact that more and more communities are affected by it, has raised public awareness. We develop a new database consisting of different sea‐level components, representing different processes, and analyze their contribution to HTF. We find, for example, that ocean tides are the main driver for HTF along the U.S. west coast, while surges are relatively more important along the east coast. Due to SLR, fewer sea level components can combine to lead to HTF at present‐day compared to the past. Correlation between the different sea‐level components also causes compounding effects leading to more (or fewer) HTF events in certain locations. The new database and analysis that is presented here advance our understanding of the role of different sea‐level processes in causing HTF along the U.S. coastline. Key Points: A novel water level decomposition method is used to develop a database of the contributions of different sea level processes to water levels Fewer sea level components can combine to push water levels above high‐tide flooding (HTF) thresholds due to sea‐level rise Co‐variability between sea‐level components leads to compounding effects causing additional (or fewer) HTF events